Policy perception of Chinese private firms and corporate investment efficiency: evidence from textual analysis - Dongmin Kong; Lu Shi (China Journal of Accounting Studies, 2024)
The policy environment is important for corporate development. This paper extracts forward-looking disclosures from annual financial reports of Chinese private listed firms, and uses a textual similarity index by employing textual analysis tools, then constructs a novel measure to capture the level of policy perception of private firms. From the view of textual similarity, this paper investigates the impact of firms’ policy perception on investment efficiency. Empirical results show that private firms with high policy perception presented in forward-looking statements are more likely to improve future investment efficiency. The main mechanisms are the spillover effect of information disclosure and the decrease on corporate uncertainty; however, more government subsidies probably reduce the positive influence of policy perception. After robustness checks, we obtain consistent results. Further evidence indicates that the positive effect of policy perception is more pronounced in financially constrained firms, and firms with less managerial myopia.